Performance Evaluation of Ammonia Refrigeration Systems in a Texturizing Plant - Abdul Cholik; Nanang Ruhyat; Sentot Novianto (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
This study evaluates the performance of an ammonia refrigeration system used as a cooling medium in a texturizing plant. The analysis was conducted over a 10-day period, focusing on key performance indicators such as compressor work, condenser exhaust heat, refrigeration effect, mass flow rate, Coefficient of Performance (COP), and overall system efficiency. The data revealed that the system performed optimally on Day 5, achieving a peak efficiency of 91%, with compressor work at 304.1 kJ/kg and condenser exhaust heat at 1414.6 kJ/kg. In contrast, the lowest efficiency was recorded on Day 3, at 77%. The refrigeration effect reached its highest value of 491.3 kJ/kg on Day 3, highlighting efficient heat absorption despite lower overall system efficiency. On Day 4, the mass flow rate was 0.001049929 kg/s, with an actual COP of 1.39, while the ideal COP peaked on Day 10 at 1.69, reflecting the system’s theoretical maximum efficiency under optimal conditions. The study emphasizes the critical role of the condenser in the system’s performance. Optimizing the condenser’s operation by controlling temperature, pressure, and flow rates, alongside regular maintenance, significantly impacts system efficiency. The findings suggest that careful monitoring of operational parameters, including compressor work and refrigerant flow, can enhance the overall efficiency and reliability of ammonia refrigeration systems in industrial settings. This research provides practical insights into improving the cooling performance, reducing energy consumption, and ensuring consistent production quality in texturizing plants.